Răspuns :
a+b=2
a²-b²=104 sau (a-b)(a+b)=104 sau 2(a-b)=104 sau a-b=52 =>a=52+b
52+b+b=2
2b=2-52
2b=(-50) =>b=(-25) =>a=27
a²-b²=104 sau (a-b)(a+b)=104 sau 2(a-b)=104 sau a-b=52 =>a=52+b
52+b+b=2
2b=2-52
2b=(-50) =>b=(-25) =>a=27
a+b=2
a²-b²=104
dar a²-b²=(a-b)(a+b) ⇒ (a-b)×2=104⇒a-b=52
a+b=2 (1)
a-b=52 (2)
se aduna (1) si (2)
2a=54⇒a=27
dar a+b=2 ⇒27+b=2⇒b=-25
deci a = 27 si b= - 25
verificare
a+b=2⇒27-25=2
a²-b²=104
dar a²-b²=(a-b)(a+b) ⇒ (a-b)×2=104⇒a-b=52
a+b=2 (1)
a-b=52 (2)
se aduna (1) si (2)
2a=54⇒a=27
dar a+b=2 ⇒27+b=2⇒b=-25
deci a = 27 si b= - 25
verificare
a+b=2⇒27-25=2